2011
DOI: 10.5152/jtgga.2011.37
|View full text |Cite
|
Sign up to set email alerts
|

Leptin expression in proliferative, secretory and hyperplastic endometrial tissues

Abstract: Objective:The goal of this study was to detect endometrial leptin expression in proliferative and secretory phases and then to compare the results with that of hyperplastic endometrium. Material and Methods:Seventeen proliferative, 23 secretory phase and 18 hyperplastic endometrial tissues diagnosed in our hospital between 2002 and 2007 were included in the study. These samples were stained with leptin antibody using an immunohistochemical method. Endometrial glandular and surface epithelium and stroma were ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Also, in the study of Ozler (2011), no difference was noticed in the intensity of staining among proliferative, secretory, and hyperplastic endometrium ( P <0.05), therefore, it was concluded that leptin does not play a role in the hyperplastic change of the endometrium ( 29 ). This result was contrary to our results.…”
Section: Discussionmentioning
confidence: 95%
“…Also, in the study of Ozler (2011), no difference was noticed in the intensity of staining among proliferative, secretory, and hyperplastic endometrium ( P <0.05), therefore, it was concluded that leptin does not play a role in the hyperplastic change of the endometrium ( 29 ). This result was contrary to our results.…”
Section: Discussionmentioning
confidence: 95%
“…Epidemiologic studies suggest that the risk of progression to malignancy is low for hyperplasia without atypia, whereas atypia is associated with a significant risk of carcinoma. Despite numerous studies on endometrial tumorigenesis, little is known about the cause of progression from endometrial hyperplasia to carcinoma [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of these tumors are of the endometrioid type that are typically hormone sensitive and have an excellent prognosis. Although hormonal and genetic association studies have been performed, the pathophysiology of ECa is still unclear (2)(3)(4). Nitric oxide synthase (NOS), which has three isoforms, catalyzes the oxidation of L-arginine to nitric oxide (NO) and citrulline.…”
Section: Introductionmentioning
confidence: 99%